Social Insurance as a Legal Phenomenon. The Historical-Legal Aspect of Its Formation and Development (from the Ancient Times till the Middle Ages) - Bodnaruk, Mykola (the Journal of Eastern European Law, 2017)
Mutual assistance, as a universal ontological phenomenon, is typical for almost all living beings possessing some intellect. It also appears in wildlife at the reflex level; however, a synthesizing sign of mutual help is a certain extent of affinity between various fauna representatives. On the other hand, the above-mentioned phenomenon does not occur neither at the level of interspecific communication, nor even at the level of the representatives of different animal groups that directly belong to the same species. We suppose that the phenomenon of mutual help is inherent only to a human being and appears between the individuals, who have no communication channels with each other. Even more, it occurs between the individuals, who do not know of the existence of each other. The phenomenon under discussion is in constant progress. It has acquired various forms, which might be united into a single ontological-legal notion – social insurance. Nevertheless, mutual assistance has undergone a few stages of its own evolution, in the course of which it has worked out certain mechanisms and forms of social insurance. As historical experience shows, mutual help appeared in very ancient times, when Homo sapiens started realizing that his species is doomed to extinction, having no chances for progressive evolution. This understanding has stipulated the fact that capable community members began sharing the results of their labor with other representatives of their social group, the latter having lost, due to some reason, the opportunity to make a living. Mutual help arose not due to the labor tools perfection, which usually caused some “product surplus”, but much earlier, when one human being began sharing his own limited and insufficient means of living with others. Numerous archeological excavations have discovered the remnants of ancient people, which testifies that disabled and injured representatives of a society received the necessary livelihood from others (healed limb fractures, absence of limbs, spine injuries, with which the individuals kept their existence are a good proof of it). That is why, it is possible to make a conclusion that the phenomenon of mutual help appeared very long ago. With the flow of time, it has turned into the factor of social insurance, the latter notion, as well as its formation and development being the focus of the article under discussion.
Keywords: взаємодопомога; соціальне страхування; право соціального забезпечення; страхування; історія права; взаимопомощь; социальное страхование; право социального обеспечения; страхование; история права; mutual help; social insurance; Social Security Law; insurance; History of Law